2012
DOI: 10.7763/ijmlc.2012.v2.256
|View full text |Cite
|
Sign up to set email alerts
|

Improving Customer Relationship Management Using Data Mining

Abstract: Abstract-Customer Relationship Management (CRM) refers to the methodologies and tools that help businesses manage customer relationships in an organized way. Data Mining is the process that uses a variety of data analysis and modeling techniques to discover patterns and relationships in data that may be used to make accurate predictions. It can help you to select the right prospects on whom to focus. The essence of the information technology revolution and, in particular, the World Wide Web is the opportunity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
1
6
0
2
Order By: Relevance
“…This research paper showed that more than 81% of participants agreed that scientific research helps in solving many of the problems of the society. This finding supports many studies in literature like Gupta and Aggarwal (2012) and Fox (2010). The answers to the main research questions are presented below in the order it appeared in the literature review of this paper.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This research paper showed that more than 81% of participants agreed that scientific research helps in solving many of the problems of the society. This finding supports many studies in literature like Gupta and Aggarwal (2012) and Fox (2010). The answers to the main research questions are presented below in the order it appeared in the literature review of this paper.…”
Section: Resultssupporting
confidence: 93%
“…Statistics is usually not studied for its own sake; it is a widely employed tool, and a highly valuable one, in the analysis of problems in natural, physical and social sciences. Further that statistical methods are nothing but a refinement of everyday thinking (Gupta and Aggarwal, 2012). They are especially appropriate for handling data which are subject to variations that cannot fully be controlled by experimental method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impor data dilakukan tahap 6 dan tahap 7 sesuai dengan tahap-tahap perancangan data mining yang terdapat dalam tulisan Gupta dan Anggarwal (2012). Pada tahap 6, aplikasi data mining yang sudah dibuat dievaluasi untuk melihat apakah aplikasi data mining yang sudah dibuat dapat membantu menjawab permasalahan bisnis bank.…”
Section: Desain Sistem Dengan Data Miningunclassified
“…Terdapat beberapa cara untuk meningkatkan nilai pelanggan, yaitu (1) meningkatkan nilai dari produk yang pelanggan punyai, (2) menjual produk yang baik kepada pelanggan, dan (3) tetap menjaga hubungan dengan pelanggan untuk jangka waktu yang lama (Rygielski et al, 2002). Secara sederhana customer relationship management dapat diartikan sebagai bagai-mana manajemen perusahaan berinteraksi dengan pelanggan dan bagaimana membangun sebuah hubungan yang efektif dengan pelanggan (Gupta dan Anggarwal, 2012).…”
Section: Manfaat Untuk Customer Relationship Management Customer Profunclassified
“…The Generic Model of Effective CRM [9] 1) Data gathering and organization: Individual customer data is gathered and organised for analysis. Data that considers customer motivations, like purchasing patterns and complaints is especially important.…”
Section: Model Of Crmmentioning
confidence: 99%